Parent-Teacher Association Intervention Strategies and Goal Achievement in Public Secondary Schools - Adeseko Sunday OLAIFA; Usamatu ABDULKAFEEL; Leonard SHAIBU; Ebunlomo Oreoluwa OLAIFA; Moses Adeleke ADEOYE (Unib Press, 2024)
Parent-Teacher Association has ensured and improved the quality and standard of education in Nigeria. This study examined parent-teacher association intervention strategies and goal achievement in public secondary schools in Ilorin-West Local Government Area, Kwara State, Nigeria. The study adopted a descriptive survey of correlational type. Two research questions and one hypothesis were raised to guide the study. A purposive random sampling technique was used to select two hundred and thirty-seven respondents from 39 public senior secondary schools in Ilorin-West Local Government Area, Kwara State. The research instrument was titled Parent-Teacher Association Intervention Strategies Questionnaire (PTAISQ) and Goal Achievement Questionnaire (GAQ) was used to collect data for the study. Descriptive statistic of frequency counts, percentages, mean and standard deviation was used to analyze demographics and answer the research questions raised. Inferential statistics of Pearson Product Moment Correlation statistics were used to test the formulated research hypotheses. The findings of the study revealed that; the level of parents-teachers’ intervention strategies were high based on the dimensions in Ilorin-West Local Government Area, Kwara State. The level of goal achievement in public secondary schools in Ilorin-West Local Government Area, Kwara State was high. There was a significant relationship between parents-teacher intervention strategies and goal achievement in public secondary schools in Ilorin-West Local Government Area, Kwara State. It was recommended among others that the Kwara State government through Kwara Teaching Service Commission (TESCOM) ensure that qualified and competent teachers are recruited so that effective and efficient teaching and learning processes will be improved.